The effect of warehouse receipt finance on farmers' terms of trade: Evidence from India - Beata Itin-Shwartz; Ayyāl Qimḥî (Bar-Ilan University, Department of Economics, 2024)
We study the effect of warehouse receipt financing on terms of trade for farmers. With limited access to credit and storage facilities, farmers are compelled to sell their produce immediately after harvest at unfavourable prices. Warehouse receipt systems allow farmers to obtain loans with the crop kept in the warehouse as collateral. Using detailed price data from rural crop markets across India, we assess the effectiveness of a reform passed in 2007 to establish a warehouse receipt system, in improving crop prices for farmers and reducing seasonal price volatility. We compare outcomes in markets in close vicinity to a new program warehouse in the period after the warehouse registered to the program, to the period before and to markets further away from a program warehouse in both periods. We find a positive and persistent effect of warehouse receipt financing on prices received by farmers, and a reduction in inter-seasonal price volatility as a result of the treatment.
Keywords: 330; Post-harvest credit; Diff-in-diff; Agricultural markets; Price seasonality; Storage